C# data structures and algorithms : explore the possibilities of C# for developing a variety of efficient applications - Jamro, Marcin (Packt Publishing, 2018)
A complete guide on using data structures and algorithms to write sophisticated C# code About This Book Master array, set and map with trees and graphs, among other fundamental data structures Delve into effective design and implementation techniques to meet your software requirements Explore illustrations to present data structures and algorithms, as well as their analysis in a clear, visual manner. Who This Book Is For This book is for developers who would like to learn the Data Structures and Algorithms in C#. Basic C# programming knowledge would be an added advantage. What You Will Learn How to use arrays and lists to get better results in complex scenarios Implement algorithms like the Tower of Hanoi on stacks of C# objects Build enhanced applications by using hashtables, dictionaries and sets Make a positive impact on efficiency of applications with tree traversal Effectively find the shortest path in the graph In Detail Data structures allow organizing data efficiently. They are critical to various problems and their suitable implementation can provide a complete solution that acts like reusable code. In this book, you will learn how to use various data structures while developing in the C# language as well as how to implement some of the most common algorithms used with such data structures. At the beginning, you will get to know arrays, lists, dictionaries, and sets together with real-world examples of your application. Then, you will learn how to create and use stacks and queues. In the following part of the book, the more complex data structures will be introduced, namely trees and graphs, together with some algorithms for searching the shortest path in a graph. We will also discuss how to organize the code in a manageable, consistent, and extendable way. By the end of the book,you will learn how to build components that are easy to understand, debug, and use in different applications. Style and approach Readers will be taken through all the indispensable data structures and algorithms so they can begin their coding journey in C#. At each step, the book will show how to implement these via examples while also discussing the attributes of each algorithm so readers are capable to make an informed choice. Downloading the example code for this book You can download the example code files for all Packt books you have purchased from your account at http://www.PacktPub.com. If you purchased this book elsewhere, you can visit http://www.Pac...